Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1016/j.jpainsymman.2011.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Prescribing Practices Can Be Improved by Low-Cost Point-of-Care Decision Support

Abstract: Context Codeine has become a controversial choice for analgesia in children compared to other commonly available drugs. Objectives To evaluate whether an educational campaign shifted resident prescribing patterns away from codeine toward more appropriate analgesics. Methods Our intervention consisted of a pocket-sized reference card given to all trainees and key staff on an inpatient pediatric acute care unit; pediatrics residents also had the option to attend a one-hour lecture. The pocket-card recommende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Several previous studies have shown that low-cost point-of-care decision support tools in the form of a pocket cards can change prescribing practices. 11,13 Utilization of the PCA order set by our pain service is consistent with a study by Overhage et al that showed that embedding “corollary orders” into the computerized physician order entry system can decrease prescribing errors of omissions. 14 Our findings are consistent with previous studies that demonstrate changes in prescribing practices through various forms of clinical decision support.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Several previous studies have shown that low-cost point-of-care decision support tools in the form of a pocket cards can change prescribing practices. 11,13 Utilization of the PCA order set by our pain service is consistent with a study by Overhage et al that showed that embedding “corollary orders” into the computerized physician order entry system can decrease prescribing errors of omissions. 14 Our findings are consistent with previous studies that demonstrate changes in prescribing practices through various forms of clinical decision support.…”
Section: Discussionsupporting
confidence: 84%
“…Whereas Ury et al showed that an educational curriculum alone was unable to improve prescribing rates of an empirical bowel regimen among trainees, 12 Rosenbluth and colleagues demonstrated that the use of pocket-sized reference card was effective in changing opioid prescribing practices in both medical and surgical trainees. 11 Increasing the prescribing rates of prophylactic bowel regimen among the surgical services will likely need to involve other modalities, such as clinical decision support tools or changes to our electronic ordering system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A quality improvement initiative with resident physicians showed a statistically significant decrease in rate of codeine prescription from 13.5% to 5.4% with the introduction of a pocketsized analgesic reference card. 34 Other interventions may include removal of codeine from hospital formularies or electronic medical record-based decision support for providers. A study by O'Conner et al found formulary restriction, supported by education and computerized order entry, effectively eliminated analgesic meperidine use at a tertiary-care hospital.…”
Section: Figurementioning
confidence: 99%
“…Preliminary evidence suggests that opioid dosing guidelines and/or physician training may reduce opioid dosage, as well as change opioid prescribing practices . However, this evidence is limited to a small number of states and a handful of clinics.…”
Section: Introductionmentioning
confidence: 99%